3D/4D printed bio-composites reinforced by bamboo charcoal and continuous flax fibres for superior mechanical strength, flame retardancy and recoverability - Mahdi Bodaghi; Kaveh Rahmani; Mohammadreza Lalegani Dezaki; Callum Branfoot; Jon Baxendale (Polymer Testing)
This study explores development and 3D/4D printing of environmentally friendly bio-composites with enhanced mechanical properties, flame retardancy, and shape memory capabilities. Composite filaments were created by incorporating polylactic acid (PLA) with bamboo charcoal (BC) and then printed using a modified printer equipped with a dual-feed system to accommodate both PLA/BC filaments and continuous flax fibres (CFF). SEM revealed strong fibre-matrix bonding with minimal voids, indicating good interfacial adhesion. Bio-composite properties were characterised through DMA, tensile, three-point bending, flammability, and shape-memory effect tests. Adding 3 wt% BC and CFF significantly increased the tensile strength by 248 % and the flexural strength by 207 % compared to pure PLA. Flame retardancy properties were notably improved, with a 50 % reduction in the burning rate, and underwriters’ laboratories (UL-94) rate and limiting oxygen index (LOI) reached to V-1 rating and 36.8%vol, respectively. DMA tests showed an increase in storage modulus, indicating improved stiffness. Shape memory tests under cold/hot programming protocols demonstrated efficient shape fixation with shape recovery ratios reaching up to 98.9 % for pure PLA and 89 % for PLA/BC/CFF for hot programming. Finally, a conceptual meta-bio-composite was 4D printed, showcasing key achievements such as quasi-zero stiffness, constant force behaviour, enhanced energy absorption/dissipation, and excellent recoverability and reusability. This highlights their potential for applications requiring durability, safety, comfort, and sustainability in sectors such as automotive, aerospace, logistics, construction, and furniture.